2022
DOI: 10.1017/jfm.2022.465
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of smooth body flow separation topography and topology on a two-dimensional geometry of finite span

Abstract: A smooth body, adverse pressure gradient (APG), turbulent boundary layer (TBL) separation is experimentally studied. The geometry features canonical TBL development prior to encountering a smooth, two-dimensional convex ramp geometry of finite span onto which a streamwise APG that is fully adjustable is imposed. Both large- and small-scale separations are studied, and all data are archived on the NASA Turbulence Modeling Resource website. This paper describes the large-scale separation case with focus on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…3.5 Interactions between crossflow structures and surface pressure Fairlie (1980) and Simmons et al (2022) suggested that pressure gradients and surface curvature are the two driving factors responsible for generating separated, coherent 3D structures. Simultaneously, the pressure distribution is influenced by the projection of the separation onto the model surface.…”
Section: Vortex Dynamics: Stretching and Tiltingmentioning
confidence: 99%
“…3.5 Interactions between crossflow structures and surface pressure Fairlie (1980) and Simmons et al (2022) suggested that pressure gradients and surface curvature are the two driving factors responsible for generating separated, coherent 3D structures. Simultaneously, the pressure distribution is influenced by the projection of the separation onto the model surface.…”
Section: Vortex Dynamics: Stretching and Tiltingmentioning
confidence: 99%
“…A more recent validation test case comes in the form of an experiment of the flow over a smooth backward-facing ramp by Simmons et al [24,28]. The ramp geometry in this test was two-dimensional, and the three-dimensionality was caused by the effect of sidewall separation on the core flow, with the aspect ratio being intentionally low.…”
Section: Three-dimensional Flow Over a Smooth Backward-facing Rampmentioning
confidence: 99%
“…The final set of computational studies in this section is dedicated to the experiment that was conducted and recently published by the authors of [24]. This test featured a separated flow over a smooth backward-facing ramp, and while the ramp itself was two-dimensional, the resulting separation was three-dimensional due to the influence of symmetrical sidewalls.…”
Section: Simulations Of the Three-dimensional Flow Over A Smooth Back...mentioning
confidence: 99%
“…Similarly, transverse or longitudinal grooves placed rearward of bluff bodies can reduce form drag (Howard & Goodman 1985. Recent experiments by Simmons et al (2022) have examined the TBL with APG and large-scale flow separation over a smooth two-dimensional convex (backward-facing) ramp with sidewalls detailing the highly three-dimensional flow through inspection of near-wall topography and topology of both separation and reattachment. Their study highlights that two counter-rotating vortical structures (secondary flow) dominate the resulting flow separation.…”
Section: Introductionmentioning
confidence: 99%
“…Their study highlights that two counter-rotating vortical structures (secondary flow) dominate the resulting flow separation. The secondary flow described by Simmons et al (2022) may relate to that occurring at a smaller scale on top of the longitudinal grooves; this secondary flow will be examined here in some detail. Song & Eaton (2002) (experimentally) and Wu & Piomelli (2018) (numerically) found that a TBL with a strong APG over a random rough surface results in earlier flow separation and delayed reattachment, contrasting that of an organized roughness such as riblets.…”
Section: Introductionmentioning
confidence: 99%